KAJIAN PEMISAHAN MINYAK - LEMAK PADA LIMBAH BUATAN DENGAN MENGGUNAKAN TEKNOLOGI DISSOLVED AIR FLOTATIONS (DAF) - Aghsoni, Fanan (Institut Teknologi Adhi Tama Surabaya, 2024)
An oil spill in seawater can pose a significant problem for the process of converting seawater into clean or drinking water. The separation of oil and fats must be carried out as an initial stage (pre-treatment) in the clean or drinking water treatment process. The Dissolved Air Flotation (DAF) system is an appropriate technology for removing oil and fats from raw water, utilizing aeration to create air bubbles in the water that lift the oil and fats to the surface for separation. Seawater characterization includes physical, chemical, and microbiological properties. The research variables in this study include initial oil concentrations (25 mg/L, 50 mg/L, and 100 mg/L), air supply pore sizes (0.5 mm, 1 mm, and 1.5 mm), air supply pressures (0.005 MPa, 0.01 MPa, and 0.015 MPa), and aeration times (30 minutes, 60 minutes, 90 minutes) in the DAF reactor to determine the effect of these variables on oil removal efficiency. Increasing the initial oil concentration leads to a higher pollutant load in the DAF flotation system, resulting in a decrease in the efficiency of the DAF process. On the other hand, smaller air supply pore diameters play a crucial role in increasing oil removal efficiency, as the reduction in pore size significantly impacts the formation of microbubble sizes, thereby providing a larger surface area to lift oil particles from the feed solution.